Biologics and surgical outcomes in Crohn’s disease: is there a direct relationship? - Quaresma, Abel Botelho (Therap Adv Gastroenterol, 2020)
Despite significant advances in medical therapy in the management of Crohn’s disease (CD), surgery is still required in a significant proportion of patients and constitutes an important tool in treatment algorithms. Recently, more options of biological agents have been made available, and most patients with CD undergoing surgical procedures have been previously exposed to this class of drugs. There is controversy in the literature as to whether anti-tumor necrosis factor (TNF) agents, anti-integrins, or anti-interleukins (ILs) have a direct relationship with increased postoperative complications. In this narrative review, the authors summarize the most important data regarding the effect of biologics on postoperative outcomes in CD. Most studies (with different designs) are based on the experience with anti-TNF agents, mostly with infliximab. Some studies outlined the relationship between vedolizumab and postoperative complications, and there is a lack of data with ustekinumab in this scenario. Most studies are retrospective, but few prospective data are available. A cause–effect (proof of concept) direct relationship between biologics and an increase in postoperative morbidity has not been demonstrated to date. Several confounding factors such as previous use of steroids, malnutrition, and unfavorable abdominal conditions have a definitely effect on postoperative complications in CD. Biologics seem safe to be used in the perioperative period, but available data are still controversial. Multidisciplinary individualized decisions should be made on a case-to-case basis, adapting the surgical strategy according to risk factors involved.